2019
DOI: 10.1038/s41598-019-48621-3
|View full text |Cite
|
Sign up to set email alerts
|

High-performance visible light photodetectors based on inorganic CZT and InCZT single crystals

Abstract: Herein, the optoelectrical investigation of cadmium zinc telluride (CZT) and indium (In) doped CZT (InCZT) single crystals-based photodetectors have been demonstrated. The grown crystals were configured into photodetector devices and recorded the current-voltage ( I-V ) and current-time ( I-t ) characteristics under different illumination intensities. It has been observed that the photocurrent generation mechanism in both photodetector devices is dominantly driven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(31 citation statements)
references
References 60 publications
1
30
0
Order By: Relevance
“…It has been reported that at this certain bias voltage, all photogenerated carriers start to participate in photocurrent. 32 In this work, no free carriers are left to participate in photocurrent beyond −4 V at a light intensity of 17.9 W/m 2 .…”
Section: ■ Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…It has been reported that at this certain bias voltage, all photogenerated carriers start to participate in photocurrent. 32 In this work, no free carriers are left to participate in photocurrent beyond −4 V at a light intensity of 17.9 W/m 2 .…”
Section: ■ Resultsmentioning
confidence: 90%
“…The external quantum efficiency (EQE), responsivity, and sensitivity values of the devices with various post-annealing temperatures for 5 at % Co-doped ZnFe 2 O 4 thin film deposition are shown in Figure b. The responsivity ( R ) and EQE are calculated by eqs and where I ph is the photocurrent, P is the light power intensity, A is the effective area of the device, and T is the transmission of the oxide thin films. Sensitivity is another crucial characteristic of a photodetector, which is related to the signal-to-noise ratio.…”
Section: Resultsmentioning
confidence: 99%
“…The quantum efficiency is an additional factor used to analyse the performance of the device. The can be defined as the fraction of incident photons which contribute to the external photocurrent [ [56] , [57] , [58] ]. here h is plank constant, c is light speed, R is responsivity, q is electron charge and is used light wavelength.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed mechanism for this effect is discussed later in this section. The photoresponsivity (R) and specific detectivity (D*) of the PDs under various UV intensities (λ = 365 nm, V bias = 1 V) are calculated using eqs and , where Δ I = I light – I dark ; I dark and I light are the measured PD currents under dark and illuminated conditions, respectively, P 0 is the power of the incident light, A is the active area of the device, and q is the elementary charge. The results of these calculations are presented in Figure c,d.…”
Section: Results and Discussionmentioning
confidence: 99%